Sosialisasi Pembelajaran Inovatif dengan Strategi Literasi di SMP se-Kabupaten Batanghari - Hilman Yusra; Albertus Sinaga (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2023)
Innovative learning is learning that is applied in the digitalization 4.0 era by focusing on strategies, methods or efforts to increase all positive abilities in the process of developing student competencies. Innovative learning provides more opportunities for students to be more active in learning and demonstrates the ability to be independent in solving a problem and conducting mediation with colleagues. Through the literacy program learning is considered to be able to increase the activity of students in the learning process. The socialization was carried out to 20 junior high school Indonesian teachers in Muaro Jambi Regency. Implementation is done by the method of question and answer and discussion. The results of the socialization show that teachers still have not properly implemented the School Literacy Movement (GLS) program so that socialization shows the teacher's stability in understanding literacy. By giving 10 minutes before learning by freeing students in iteration. Through habit will foster its own innovation for students. It is recommended for teachers to always apply literacy time before carrying out learning.